Kemampuan Literasi Kitab Kuning pada Santri Pondok Pesantren Madrasah Tsanawiyah Alliful Ikhwan Silangkitang Labuhan Batu Selatan - Hasibuan, Enriani; Ritonga, Sakti; Yusniah, Yusniah (TSAQOFAH, 2023)
The purpose of this study was to find out how the students of Alliful Ikhwan Silangkitang Labuhan Batu Selatan Islamic Boarding School Students are able to access, evaluate, and use information on the contents of the tallow book with international literacy standards. The results showed that the results of this study, namely the ability of the Alliful Ikhwan Silangkitang Islamic Boarding School students to access information on the yellow book is quite good, this can be seen from the information obtained from discussing with the teacher and ustadz and also with friends, then the information obtained is then sorted and selected to be applied in everyday life. The ability of Islamic boarding school students to evaluate information on the yellow book is quite good. It can be aeen that to get clear information, everyone has different versions, some choose and sort the information first, and some directly use the information.